PENGARUH PROFITABILITAS, LEVERAGE DAN KEBIJAKAN DIVIDEN TERHADAP KEPUTUSAN INVESTASI Studi Empiris pada Perusahaan Manufaktur Sub Sektor Farmasi yang Terdaftar Di Bursa Efek Indonesia periode 2015-2019. - Hasanah, Wardatul; Sutjahyani, Dewi (JEA17: Jurnal Ekonomi Akuntansi, 2021)
This research aims to explore the impact of profitability, leverage, and dividend policy on investment decisions. This research was conducted on pharmaceutical sub-sector manufacturing companies listed on the Indonesia Stock Exchange during 2015-2019. The number of samples used in this study is as many as 6 companies with purposive sampling method. The data analysis technique used is multiple linear regression analysis. The results of this study show that profitability variables have no effect on investment decisions, leverage variables positively affect investment decisions, and dividend policy variables have no effect on investment decisions